Analisis Hukum Islam dan Hukum Positif Terhadap Pembatalan Sepihak Perjanjian Sewa Menyewa - Dian Restu Salsabila; Karimatul Khasanah; Heny Rahmawati (Fakultas Syariah Universitas Islam Negeri (UIN) K.H. Abdurrahman Wahid Pekalongan, 2022)
A house rental agreement is something that is commonly done by the community. One of them is renting a house in Kasaba Housing, Jalan Kanfer 1 No. 6, Kalisalak Village, Batang District. In practice, there is a unilateral cancellation in the agreement made by the lessee. This is of interest to in-depth analysis of unilateral cancellations made by tenants. This research is a field research, with a qualitative approach. The results of this study indicate that the implementation of a house rental agreement in Kasaba Housing Jalan Kanfer 1 No. 6 Kalisalak Village, Batang District is in accordance with the terms and pillars of the lease agreement in Islamic law and also in accordance with the terms of the agreement in Article 1320 of the Civil Code. However, regarding the legal consequences of unilateral cancellation in the lease agreement carried out by the lessee according to Islamic law, namely the end of the contract due to termination which was phased based on mutual agreement (al-iqalah) making the parties who entered into the lease contract return to their original status as before the occurrence. contract. Meanwhile, according to positive law, a legal act that unilaterally cancels an agreement is contrary to Article 1570 of the Civil Code.